Pengaruh Kecerdasan Emosional, Organizational Citizenship Behavior (OCB) dan Kepuasan Kerja Terhadap Kinerja Karyawan pada PT PLN (Persero) Area Bojonegoro - MUSTIKA WATI, DANA; SURJANTI, JUN (Jurnal Ilmu Manajemen (JIM), 2018)
In a world of electricity today, human resources hold an important roles. Acompany will have many problems if the quality of human resources is inadequate.Although the support of facilities, infrastructure and adequate human resources are available and there are no support of competent human resources in their respective job`s division, the organization`s activity will have not done properly. It means that human resources are the key which must be managed properly, the company must pay attention to human resources such as emotional intelligence, organizational citizenship behavior and job satisfaction to help company in achieving goals. The Objectives of this research are to examine and analyze the effect of emotional intelligence, organizational citizenship behavior and job`s satisfaction on employ`s performance at PT PLN (Persero)Bojonegoro`s area .This research is a quantitative research with the total sample of 63 employees. The measurement tools used are interviews, observations and questionnaires. Beside that,the statistic`s analysis used in this study is Partial Least Square (PLS) technique with the help of SmartPLS 3.0 program and Statistical Package for the Social Science (SPSS) software. The measurement scale used is Likert Scale.The results of this study explain that emotional intelligence significantly and positively affect employ`sperformance.Beside that, the organizational citizenship behavior has a significant and negative impact on employ`s performance and the job`s satisfaction have a significant and positive effect on employ`s performance. Keywords : Emotinal intelligence, organizational citizenship behavior, job`s satisfaction ,employ`s performance.